Long-lived collateralized assets and bubbles - Aloisio Araujo; Mário R. Páscoa; Juan Pablo Torres-Martínez (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2007)
When infinite lived agents trade long-lived assets secured by durable goods, equilibrium exists without any uniform impatience requirements or additional debt constraints. Asset pricing bubbles are absent when the new endowments of durable goods are uniformly bounded away from zero. Otherwise, bubbles may occur, even for assets in persistently positive net supply and for deflators that yield finite present values of aggregate wealth.
Keywords: D50; D52; 330; Existence of equilibrium; Asset pricing bubbles; Collateralized assets.; Kapitalmarkttheorie